FACTORS IN LEARNING MANAGEMENT SYSTEM TO OUTREACH ONLINE LEARNING ALUMNI ENGAGEMENT IN HIGHER EDUCATION - Shiyrah Theosebes Sela; Ridho Bramulya Ikhsan; Yuniarty (INFOTECH journal, 2024)
The global education will not be limited to a place, time and condition. A non-state university in Indonesia through its online learning makes it happened so everyone can experience learning. In providing high quality education, this non-state university facilitates the learning process with Learning Management System equipped with features that will support students. This support will strengthen the bonds between the students and the university even after graduation. The uniqueness of this paper is aiming to find out the essential factors of the Learning Management System that outreach alumni engagement in online learning, not regular type of students, and how the factors work through the Learning Management System. The online learning students interact and collaborate virtually with the lecturers, among students, administration staff, and so on that will impact to the bonds or the sense of belongings among them. A questionnaire with open questions, was distributed through social media to the online learning students. The questionnaire was created using Microsoft Forms and Mentimeter. Mixed method was used to analyze data collected. Quantitative method was used to calculate the data and then quantitative method for interpreting the findings. The findings which are the essentials factors to outreach alumni students will be benefits for the university, online learning institutions, also other parts that required the information to manage the alumni to create alumni engagement.